2018
DOI: 10.1016/j.ijnss.2017.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to improve communication between nurses and physicians in the intensive care unit: An integrative literature review

Abstract: Effective communication among healthcare professionals in the intensive care unit (ICU) is a particular imperative, with accurate and efficient interdisciplinary communication being a critical prerequisite for high-quality care. Nurses and physicians are highly important parts of the healthcare system workforce. Thus, identifying strategies that would improve communication between these two groups can provide evidence for practical improvement in the ICU, which will ultimately improve patient outcomes. This in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
108
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(118 citation statements)
references
References 47 publications
6
108
0
4
Order By: Relevance
“…The proper management of healthcare to ensure safety, effectiveness, quality, sustainability and positive experiences to users and professionals fundamentally depends on communication among health professionals. Clinical documentation is an instrument for communication between these professionals (1)(2)(3) . The quality of clinical documentation has therefore been the object of policies, norms and guidelines of health services and of organizations which guide or regulate health actions.…”
Section: Introductionmentioning
confidence: 99%
“…The proper management of healthcare to ensure safety, effectiveness, quality, sustainability and positive experiences to users and professionals fundamentally depends on communication among health professionals. Clinical documentation is an instrument for communication between these professionals (1)(2)(3) . The quality of clinical documentation has therefore been the object of policies, norms and guidelines of health services and of organizations which guide or regulate health actions.…”
Section: Introductionmentioning
confidence: 99%
“…Good communication skills among pharmacists are also necessary to identify issues such as the patient's drug use, interactions, and side effects. Wang, Wan, Lin, Zhou, and Shang (2017) used an integrated review approach to analyse the effectiveness of communication between healthcare experts in the intensive care unit. It was found that efficient interdisciplinary communication is a vital requirement for quality healthcare delivery.…”
Section: Communication Issues In Healthcare Environmentmentioning
confidence: 99%
“…Considering that over the last decade, improving the quality and safety has become one of the priorities of hospitals all around the world, professional relationship between the members of the care team is one of the important and reliable indices for patient care (10), and it potentially would affect patient's safety (11). The study of Rabøl et al (2011) showed that the reason for more than half of the incidences is rooted in inappropriate verbal communication between the personnel (12).…”
Section: Introductionmentioning
confidence: 99%
“…The study of Rabøl et al (2011) showed that the reason for more than half of the incidences is rooted in inappropriate verbal communication between the personnel (12). Also, the evidence and studies have suggested that promoting relationships and cooperation in CCUs would improve the quality of care, safety, and positive outcomes in the patients (10).…”
Section: Introductionmentioning
confidence: 99%